Preparing the "soil": the primary tumor induces vasculature reorganization in the sentinel lymph node before the arrival of metastatic cancer cells. - Qian, C; Berghuis, B; Tsarfaty, G; Bruch, M; Kort, E; Ditlev, J; Tsarfaty, I; Hudson, E; Jackson, D; Petillo, D; Chen, J; Resau, J; et al. (2006)
Sentinel lymph node (SLN) metastasis is the first step in the spreading of cancer in many malignancies. Tumor-reactive lymphadenopathy in SLNs has been observed for decades, but alterations of the lymphatic channels and vasculature in these nodes before the arrival of metastatic tumor cells remain unexplored. Using animal models, we show here that, before the establishment of metastasis in the SLN, there are reorganizations of the lymphatic channels and the vasculature. The node becomes a functional blood vessel-enriched and lymph vessel/sinus-enriched organ before metastasis. The enlargement of the lymph sinuses is correlated with the primary tumor weight. The newly emerged functional blood vessels develop from high endothelial venules (HEV), in which the proliferation rate of the endothelial cells is also significantly increased. Similar alterations of the HEVs are also characterized in the axillary lymph nodes from human breast cancer patients without the evidence of metastasis. These findings support the hypothesis that modification of the microenvironment for a secondary tumor (i.e., vasculature reorganization in the SLN) can be initiated by a primary tumor before and independent of the physical presence of metastatic cancer cells.